Reconstructing the Relative Ice-Flow Chronology South of Lake Mistassini in Canada from New Ice-Flow Indicator Mapping - Mohamed El Amrani; Khadija Diani; Mohamed Hafedh Hamza; Mohamed Elhag; Said Courba; Afaf Amine; Moulay Ahmed Ben Driss; Lahcen Ousaid; Nabil Mdiker; Youssef Hahou; Larbi Boudad (Limnological Review)
Understanding paleo-ice flow chronology is essential for reconstructing past ice mass dynamics, interpreting the current landscape, and identifying the sources of Quaternary sediments in deglaciated regions. A recent systematic mapping of striated bedrock and streamlined landforms south of Lake Mistassini in Canada reveals a complex sequence of five ice flows. The earliest flow was directed to the southeast (SE) and originated from a NE-SW ice divide located northwest of Lake Mistassini at the Last Glacial Maximum. A progressive clockwise rotation of this ice divide, likely triggered during the early deglaciation, appears to have generated ice flows toward the south–southeast (SSE) and then toward the south (S). During the later stages of deglaciation, the flow originated from the Québec–Labrador Dome, initially toward the south–southwest (SSW) and then toward the southwest (SW). This study presents new data on ice flows south of Lake Mistassini and shows that the southward and south–southeastward ice events occurred before the late stage of deglaciation. This interpretation contradicts some previous studies and will contribute to the discussion on the dynamics of the Laurentide Ice Sheet in the Mistassini area and support mineral exploration efforts in the region.